The Spillovers of Competition: Value-based Activism and Political Cross-fertilization in an Indian Campus - Jean-Thomas Martelli (South Asia Multidisciplinary Academic Journal)
The recent spur of student-led mobilizations in India led to the portrayal of select public universities as the epitome of resistance, dissent and countercultural politics. Departing from essentialist approaches to student politics, this article outlines the processes by which campus spaces activate the formation of political attitudes among participants. It builds on an archival and ethnographic account of educated youth politics in one of the most politicized universities in the country, Jawaharlal Nehru University. I suggest that everyday political competition among student organizations is a central condition for the development of dissonant political participation, as it enables both inter-cohort political socialization and the spilling over of ideological idioms to the sociologically diverse student groups on campus. I argue that mechanisms of political outbidding sustained by politically enterprising student collectives nurture value-based dissent by continually emulating political counter-narratives while fostering ideational cross-fertilization.